IMPLEMENTATION OF OCCUPATIONAL SAFETY TRAINING FOR DOCTORS AT OHS TRAINING CENTER MEDAN - Sumaryanto Sumaryanto; Syamsul Arif; Osberth Sinaga; Zainuddin Zainuddin; Kisno Kisno (Jurnal Education and Development, 2023)
This study aims to find out the implementation of Occupational Health and Safety (OHS) training for company doctors at OHS Training Center Medan.; the obstacles in the implementation of OHS training of corporate doctors in OHS Training Center Medan.; the efforts implemented on the company's OHS doctor training. This research is a qualitative descriptive research and data collection techniques including, interviews, observations, and documentation. The subjects in the study were 10 people and the data validity technique used was source triangulation. The results showed that the implementation of OHS for company doctors at The OHS Training Center Medan has been carried out; the obstacles to the implementation of OHS from the human factor such as there are still participants who do not comply with the rules. Obstacles from environmental factors are; the amount of Personal Protective Equipment has not met the needs of trainees, there has been no OHS warning in the practice room, lack of instructor supervision during practice in the field; the efforts to overcome obstacles in the implementation of OHS, such as providing socialization, the availability of personal protective equipment and work safety equipment for participants, reprimanding participants who violate the rules and imposing strict sanctions for violators of the code of conduct who commit repeated violations.